UJI DAYA HAMBAT EKSTRAK DAUN MANGGA (Mangifera indica L.var. arum manis ) TERHADAP PERTUMBUHAN JAMUR Candida albicans - Maslahatun Maslahatun; Ana Andriana; Herlinawati Herlinawati; Moh. Maswan (Nusantara Hasana Journal, 2022)
Candidiasis or yeast infection is a fungal infection that occurs due to excessive fungus culture, which under normal conditions appears in small amounts. The incidence of candidiasis in Asia from several epidemiological studies in Hong Kong states that Candida albicans is the species most often identified with an average of 56% of candidiasis cases (Puspitasari, 2019). This research is an experimental study. The design carried out in this study was a Completely Randomized Design (CRD) with 4 treatment groups consisting of ethanol extracts of mango leaves (Mangifera indica L.) with a concentration of 250 μg / mL, 500 μg / mL, 750 μg / mL, 1000 μg / mL mL and 2 control groups. The extract is made by maceration method. Samples were filtered and concentrated by evaporation, then a serial concentration of 250 μg / mL, 500 μg / mL, 750 μg / mL 1000 μg / mL was carried out, after which the sensitivity test was carried out with the paper disc diffusion method using Potato Dextrose Agar. Performed four repetitions at each concentration. The average of inhibition zone area obtained at a concentration of 250 μg / mL was obtained at 6.25 mm, 500 μg / mL was obtained 8.5 mm, 750 μg / mL was obtained at 8.75 mm 1000 μg / mL at 12.25 mm. Each concentration of mango leaf extract (Mangifera indica L. var. Arum manis) contained a zone of inhibition to the growth of the fungus Candida albicans.